A Rare Case of Male Primary Breast Lymphoma - Rathod, Jawahar (Korean Breast Cancer Society, 2011)
Primary lymphoma of the breast is a rare occurrence because of the paucity of lymphoid tissue in the breast and is an even rarer entity in the male breast. Imaging, along with tissue diagnosis goes a long way in diagnosing breast lymphoma which has a significantly different management scheme than other breast neoplasms with respect to radio-chemotherapy rather than surgical resection. We present a case of primary male breast lymphoma which was evaluated with magnetic resonance imaging as well as other conventional imaging modalities and was treated by chemotherapy with a 7-month follow-up.